Soil Inorganic Phosphorus Is Closely Associated with pqqC- Gene Abundance and Bacterial Community Richness in Grape Orchards with Different Planting Years - Xue Wang; Zhubing Shao; Shuo Fang; Jieshan Cheng; Xiaotong Guo; Juan Zhang; Chunyan Yu; Tingting Mao; Guohui Wu; Hongxia Zhang (Agronomy)
The high application rate and low utilization efficiency of inorganic phosphorus (Pi) fertilizer could lead to significant P accumulation in soil. Soil P cycling is greatly affected by the planting time in perennial fruit yards. However, the mechanism by which soil Pi fractions and pqqC-harboring bacterial communities, and their relationships, are affected by the planting time of fruit vines, remains unclear. Here, the soil Pi fractions, the pqqC-harboring bacterial communities, and their relationships in the grape yards with 0.5, 4, 16 and 22 growth years, designated as Y0.5, Y4, Y16 and Y22, were examined. The results showed that with the increasing growth years, soil organic carbon (SOC) contents and pH values, respectively, increased and decreased. In addition, the contents and percentages of soil labile Pi and moderately labile Pi increased, whereas those of soil stable Pi decreased. In the soils of Y4, Y16 and Y22, the abundance and α-diversity of pqqC decreased compared to the soils of Y0.5. In the soils of Y16, the composition of pqqC-harboring bacterial communities was altered significantly, showing a great difference compared to the soils of Y0.5, Y4 and Y22. At genus level, the relative abundance of pqqC-harboring bacteria was highly correlated with soil P fractions. Further structural equation modeling revealed that the relationships between the abundance and community richness of the pqqC gene and soil Pi transformation were regulated by soil pH. These findings suggest that changes in soil Pi fractions are closely associated with soil pH, pqqC gene abundance, pqqC-harboring bacterial community richness and SOC content in grape orchards with different planting years.